2021
DOI: 10.3390/ijms22115743
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SARS-CoV-2 RNA by a Multiplex Reverse-Transcription Loop-Mediated Isothermal Amplification Coupled with Melting Curves Analysis

Abstract: Loop-mediated isothermal amplification (LAMP) is a method of nucleic acid amplification that is more stable and resistant to DNA amplification inhibitors than conventional PCR. LAMP multiplexing with reverse transcription allows for the single-tube amplification of several RNA fragments, including an internal control sample, which provides the option of controlling all analytical steps. We developed a method of SARS-CoV-2 viral RNA detection based on multiplex reverse-transcription LAMP, with single-tube quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…As it happens for PCR reaction, fluorescence-producing reactions are an important route for detecting these products of amplification optically, both in real-time ( Ganguli et al., 2020 ; Alekseenko et al., 2021 ) and in end-point ( Alekseenko et al., 2021 ; Sherrill-Mix et al., 2021 ) contexts. The mechanisms that lead to fluorescence production include intercalating dyes ( Alekseenko et al., 2021 ), specific oligonucleotide probes ( Jang et al., 2021 ; Oscorbin et al., 2021 ), or enzymatic reactions that culminate in the production of fluorescence ( Joung et al., 2020 ; Sun et al., 2021 ). Intercalating dyes, such as SYBR Green ( Alekseenko et al., 2021 ) or EvaGreen ( Alekseenko et al., 2021 ), are nonspecific but can be used for both real-time monitoring, or end-point measuring of amplification.…”
Section: Molecular Detection Routesmentioning
confidence: 99%
“…As it happens for PCR reaction, fluorescence-producing reactions are an important route for detecting these products of amplification optically, both in real-time ( Ganguli et al., 2020 ; Alekseenko et al., 2021 ) and in end-point ( Alekseenko et al., 2021 ; Sherrill-Mix et al., 2021 ) contexts. The mechanisms that lead to fluorescence production include intercalating dyes ( Alekseenko et al., 2021 ), specific oligonucleotide probes ( Jang et al., 2021 ; Oscorbin et al., 2021 ), or enzymatic reactions that culminate in the production of fluorescence ( Joung et al., 2020 ; Sun et al., 2021 ). Intercalating dyes, such as SYBR Green ( Alekseenko et al., 2021 ) or EvaGreen ( Alekseenko et al., 2021 ), are nonspecific but can be used for both real-time monitoring, or end-point measuring of amplification.…”
Section: Molecular Detection Routesmentioning
confidence: 99%
“…The work by Oscorbin et al demonstrates the ability to detect a duplex of bacteriophage MS2 RNA and the E gene of SARS-CoV-2 using intercalating dye SYTO-82. After LAMP amplification of these targets of interest and the addition of SYTO-82, a melting curve analysis was performed and demonstrated an exceptionally low LOD for the E gene (20 copies/reaction) in the duplex detection with MS2 [ 89 ]. The melting curve from this study is shown in Figure 4 c and demonstrates that multiplex detection can be achieved without any specificity of the dye.…”
Section: Readout Modalitiesmentioning
confidence: 99%
“…8 Kudr et al 4 demonstrated the potential use of electrochemical biosensors for virus identification in their review. In many studies, loop-mediated isothermal amplification (LAMP) [9][10][11][12] and highly multiplexed clustered regularly interspaced short palindromic repeats (CRISPR)-based nucleic acid detection [13][14][15][16] have been investigated as potential tools for SARS-CoV-2 detection. In addition to the above-mentioned diagnostic approaches, matrix-assisted laser desorption and ionisation with time-of-flight analyser mass spectrometry (MALDI-TOF MS) for SARS-CoV-2 detection was also demonstrated as another promising alternative in recent studies.…”
Section: Tomas Domentioning
confidence: 99%